Principles of lexicographic representation of neologisms and new phraseological units in mass-media - Shevchenko, Larysa; Syzonov, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2017)
This article identifies the peculiarities of the lexicographic analysis of new words and phraseological units in the modern Ukrainian mass media, considers the place of media lexicography in modern linguistics and also gives the principles of presentation of new phraseological units in the innovative dictionary entitled "New Media and the Phraseological Units of the Ukrainian Mass Media". The authors also present a detailed description of the dictionary’s structure, reveals stages of collection and processing the material and the principles of work with the media texts – printed, digital, advertising and radio genres. Specific attention is paid to the functional principle as the main principle of work with the media texts, since it made possible to monitor the developments in the modern Ukrainian language through mass media. Samples of dictionary articles and the detailed lexicographic descriptions are given. Also the directions of work have been suggested for lexicographists and linguists regarding work with the media texts, collecting and processing the material, which will be the basis for new dictionaries of new lexical and phraseological units.